2005
DOI: 10.1208/pt060352
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical assisted atomization: A novel technology for microparticles preparation of an asthma-controlling drug

Abstract: The objective of this study was to produce microparticles of a new asthma-controlling drug by supercritical assisted atomization (SAA), proposed as an alternative to conventional jet-milling process. SAA is based on the solubilization of supercritical carbon dioxide in a liquid solution containing the drug; the ternary mixture is then sprayed through a nozzle, and microparticles are formed as a consequence of the enhanced atomization. SAA process parameters studied were precipitator temperature, nozzle diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…It has until now been used with success to produce micronic particles of some pharmaceutical compounds, [14][15][16] also on the pilot scale. 16 Unlike other SCF-based techniques, SAA can also be used to process water-soluble compounds (eg, CS) 14,17 ; however, SAA has only occasionally been used to test anti-inflammatory compounds. 14,17 Previous supercritical studies on the micronization of CS showed that it is not soluble in SC-CO 2 ; supercritical antisolvent micronization, an SCF technique different from SAA, 8,9 was attempted using a mixture of methanol and water as liquid solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has until now been used with success to produce micronic particles of some pharmaceutical compounds, [14][15][16] also on the pilot scale. 16 Unlike other SCF-based techniques, SAA can also be used to process water-soluble compounds (eg, CS) 14,17 ; however, SAA has only occasionally been used to test anti-inflammatory compounds. 14,17 Previous supercritical studies on the micronization of CS showed that it is not soluble in SC-CO 2 ; supercritical antisolvent micronization, an SCF technique different from SAA, 8,9 was attempted using a mixture of methanol and water as liquid solvent.…”
Section: Introductionmentioning
confidence: 99%
“…16 Unlike other SCF-based techniques, SAA can also be used to process water-soluble compounds (eg, CS) 14,17 ; however, SAA has only occasionally been used to test anti-inflammatory compounds. 14,17 Previous supercritical studies on the micronization of CS showed that it is not soluble in SC-CO 2 ; supercritical antisolvent micronization, an SCF technique different from SAA, 8,9 was attempted using a mixture of methanol and water as liquid solvent. Particles ranging from 0.1 to 20 μm in diameter were obtained, in both amorphous and crystalline form.…”
Section: Introductionmentioning
confidence: 99%
“…After (S) ‐IBP loading, the nanocarriers were encapsulated into CHT microparticles by SASD. In this process, the solubilization of scCO 2 in a liquid solution containing CHT and IBP‐loaded PURE‐POx takes place and the microparticles are achieved as a consequence of the enhanced atomization of the multicomponent mixture upon spraying out through the nozzle …”
Section: Resultsmentioning
confidence: 99%
“…Due to these favorable properties, supercritical fluids (mainly supercritical carbon dioxide, SC-CO 2 ) are currently proposed in a wide range of extraction applications (Reverchon and De Marco, 2006), microparticle formation (Della Porta and Reverchon, 2007a;Della Porta et al, 2005, 2006bReverchon and Adami, 2006;Reverchon and Antonacci, 2007) and membrane drying technologies . Recently, SC-CO 2 has been also proposed to extract the organic phase of oil-in-water (O/W) or water-in-oil (W/O) emulsions.…”
Section: Introductionmentioning
confidence: 99%